(untitled) (ModaPalavra e-periódico, 2013)
This article discusses the new values for fashion in the third millennium, and aims to define conceptual bases in studies on sustainability, creative economy and solidary economy, to understand the new practices in fashion. It describes experiences in researches that are being held in the course of Fashion Design at Universidade de Caxias do Sul, social and economic results, after two and a half years of work, developed with a group of artisans will.